Webtv como ferramenta do jornalismo público: um estudo sobre a TV IFPB, TV Bem Baiano e Canal IFPB - Nunes, Juliana Gouveia de Amorim (2016)
This project aimed at analysing whether there are traces of public journalism in three WebTVs from Federal Institutes of Education, Science and Technology: TV IFPB, TV Bem Baiano e Channel IFPE. It seeks to detect the most common topics in the produced contents by these WebTVs; to gauge the influence of the official sources used to produce articles; to investigate if users are motivated to contribute at any level during the production stage. To this end, it was adopted the methodology of content analysis of the articles published by the WebTVs, from January to December 2015, totalizing 49 videos. This analysis was grounded in the categories Content in depth, Distinguish Practices in Society, Public Interest Topics, Guidance to the public/ Provision of Services and Diversified Sources, formulated based on the principles of public journalism and in accordance to the intended aims. In order to develop this project, we referred to some researchers‟ studies, such as Traquina et al. (2001), Bauman (2009), Jenkins (2006) e Becker e Mateus (2011). It is reinforced that there is not a Communication Policy which serves as guideline in the Federal Institutes of Education, Science and Technology for journalists and other professionals involved with communication and information. It was observed that, though the articles produced by the WebTVs contain aspects of public journalism, they do not foster its main characteristics, as the narratives do not generate a plural debate of ideas nor spare the citizens enough space to lead the discussions. Users‟ engagement in the process of producing the articles is also limited, taking into account the interactive possibilities that the WebTVs provide. With these results, we suggest some changes in the journalism practiced by the WebTVs as well as an open proposal for programmes along the lines of the public journalism, based on the findings of the writers who have supported this study, and appropriate for a hypermedia system that comes as part of a public institution of education.